Partial Pulpotomy to Successfully Treat a Caries-Induced Pulpal Micro-Abscess: A Case Report - Motoki, Okamoto; Fergus, Duncan Henry; Yusuke, Takahashi; Nanako, Kuriki; Matsumoto, Sayako; Mikako, Hayashi (Frontiers in Dental Medicine, 2021)
Vital pulp treatments (VPT) are therapeutic strategies aimed at conservatively managing deep carious lesions and the exposed pulp. VPT has recently expanded through the use of hydraulic-calcium-silicate cements (HCSC), cone-beam-CT, dental operating microscopy (DOM), as well as an improved understanding of pulpal repair mechanisms. Consensus documents have concluded that non-selective removal of caries is not necessary in the absence of clinical symptoms, as partial or non-selective caries removal techniques reduce the likelihood of pulp exposure. Alternatively, others suggest that leaving carious tissue may help sustain pulpal inflammation and lead to failure of VPT. The presence of a purulent discharge from the exposed pulp are considered indicative of an irreversible damage and a need for pulpectomy. This report documents the successful VPT in a symptomatic molar with caries that exhibited purulent discharge from the pulp. A female patient presented with spontaneous pain in maxillary left second molar. One-year-before, she had received a cast-metal restoration over a resin-based-composite restoration. The tooth had been largely asymptomatic since; however, after experiencing spontaneous pain, she consulted the hospital clinic. Radiographs indicated that the restoration was not deep with visible dentin between the restoration and pulp. Pulp sensibility tests yielded a positive response. There was no pain on percussion and no periodontal problems. Removal of the restoration and carious dentin using a DOM resulted in a pulpal exposure with purulent discharge and bleeding. A partial pulpotomy using HCSC was performed. Six-months later, the clinical symptoms had completely resolved; however, due to concerns of partial necrosis was re-assessed. DOM examination revealed an incomplete hard-tissue barrier; moreover, there were also signs of residual tissue with inflammation. As a result, the defected area was enlarged, the pulp tissue debrided, and the HCSC reapplied. After review at 1 year, the tooth remains symptomless, with no apical radiolucency. Notably, this report visually illustrates that exposed pulp tissue contained limited region pus can maintain vitality after VPT. This finding raises two questions: 1) whether leaving infected dentin in situ and avoiding visualization of the pulp exposure is appropriate; 2) whether the presence of purulent tissue in the pulp warrants a pulpectomy.